The Inclusion of Medical Curricula for Greater Training on the Detection and Reporting of Child Abuse and Neglect - Athena Ivanoff; Orien L. Tulp (Emerging Trends in Disease and Health Research Vol. 6, 2022)
The goal of this paper is to raise awareness of the lack of suspected child abuse and neglect (SCAN) knowledge and training among medical students, as well as to provide them with a foundation in the presentation of child abuse and neglect in the clinical setting, and to help those unfortunate children who may inadvertently fall victim to such behavior have a brighter, more positive, and secure future. Child maltreatment and neglect are becoming more common around the world. This rise has been noted in the United States and around the world, and many incidences of child abuse and neglect are considered to go unnoticed and unreported in the United States and overseas. Practicing physicians and their supporting medical professional staff including nurses, medical assistants, and mid-level providers are in a pivotal position to assess, document, initiate and report suspected child abuse and neglect (SCAN) during initial physical assessments, where the suspected injuries may easily be documented during such physical examinations.